Studi Pengetahuan Ibu Menyusui Tentang Kenaikan Berat Badan Bayi Usia 1-6 Bulan Di Puskesmas Sewon II - Annisa Sri Wahyuni; Sylvi Wafda Nur Amellia; Mahindria Vici Virahaju; Istri Bartini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The problem of growth disorders is a problem that needs specialattention. Lack of knowledge of breastfeeding mothers about weight gain will have anegative impact on the baby and will affect the mother's behavior in providing exclusivebreastfeeding to her baby.Objetive: to determine the level of knowledge and know the source of knowledge ofbreastfeeding mothers about infant weight gain aged 1-6 months.Method: This research is a quantitative descriptive study with a cross sectionalapproach. This research was conducted in May 2023 at the Sewon 2 Health Center.The population in this study were all breastfeeding mothers who had babies aged 1-6months who came to the Sewon 2 Puskesmas during the immunization schedule.Sampling using purposive sampling with a sample size of 30 nursing mothers.Result: The results showed that 60% (18 respondents) had sufficient knowledge,13.3% (4 respondents) had poor knowledge and only 26.7% (8 respondents) had goodknowledge about infant weight gain. As many as 70% (21 respondents) get theirsource of knowledge from health workers and 26.7% (8 respondents) use the MCHbook as a source of knowledge.Keywords: Baby Weight, Breastfeeding Mom, Knowledge